Pengaruh Kompetensi, Pengembangan Karir, Budaya Organisasi dan Pelatihan Terhadap Kinerja Karyawan - Basuki, Antonius Ndaru Sulistiyono (Universitas Katolik Darma Cendika, 2025)
A modern company requires employee performance that is able to achieve targets so that company goals are met. Employees as human resources in the company are expected to be able to contribute and add value.This study was conducted with the objectives of this research are (1) able to prove whether competence has a positive influence on employee performance, (2) able to prove whether career development has a positive influence on employee performance, (3) able to prove whether organizational culture has a positive influence on performance employees, (4) able to prove whether training has a positive influence on employee performance, (5) able to prove whether simultaneously competency, career development, organizational culture and training have a positive influence on employee performance. This research is classified as basic research because this research aims to test, identify, explain, modify and develop theories from previous research. Based on its objectives, this research is included in the category of causal research which is descriptive explanatory in nature and explains the influence of the independent variable on the dependent variable. This research is a quantitative type with primary data sources from research subjects, namely employees with a minimum work period of 1 year through distributing questionnaires. The sampling used is saturated/census sampling where all members of the population are used as samples. The total population is 152 people. The questionnaire uses a Likert scale measurement type with five scales consisting of strongly disagree, disagree, quite agree, agree, strongly agree with a value range of 1 to 5. Data analysis uses multiple linear regression analysis techniques using JASP 0.18.3 software. From the research results, it is partially proven that the competency and organizational culture variables have a positive and significant effect on employee performance. Meanwhile, the career development variable has a negative and significant effect on employee performance. The training variable has a negative and insignificant effect on employee performance. This research also proves that simultaneously competency, career development, organizational culture and training have a positive and significant effect on employee performance. The results of this research can be used as a basis for management to determine the company's strategic direction in the medium or long term into the future. Keywords: Employee Performance, Competency, Career Development, Organizational Culture, Training.